IDENTIFICATION OF LIGNOCELLULOSE-LIKE MATERIAL USING SPECTROSCOPY ANALYSIS - Adi, Danang Sudarwoko; Fatriasari, Widya; Narto; Triwibowo, Dimas; Darmawan, Teguh; Amin, Yusup; Sofianto, Imran Arra'd; Pari, Rohmah; Agustiningrum, Dyah Ayu; Rahmanto, Raden Gunawan Hadi; Dewi, Listya Mustika; Himmi, Setiawan Khoirul; Djarwanto; Damayanti, Ratih; Dwianto, Wahyu (Indonesian Journal of Forestry Research, 2024)
Lignocellulose materials, such as bamboo, rattan, and wood, have been largely used for furniture and crafts. On the other hand, the utilization of lignocellulose-like materials, which have a similar texture and appearance to those from nature, has been increasing recently due to their superior durability. This research aimed to identify the lignocellulose-like material using spectroscopy analysis, such as Raman and Near Infrared (NIR) which is well-known as a non-destructive, quick, and accurate approach for material identification. We investigated 4 types of lignocellulose-like materials that were provided by Dewan Serat Indonesia (The Indonesian Fiber Council) from an industry that produces them. The NIR analysis was performed at wavenumbers 10,000-4,000 cm-1. The natural lignocellulose (bamboo and wood) and the polymers (polyethylene and polyproline) were used as standards. Raman analysis was further employed to identify the composition of selected lignocellulose-like materials by comparing their spectra with the library software. The results showed that the original NIR spectra of lignocellulose-like and those natural materials were different, indicating that the NIR analysis can differentiate those materials. The NIR spectra of lignocellulose-like materials were similar to those of polyethylene spectra. Those lignocellulose-like were also identified as polyethylene due to the similarity of the Raman spectra and their library spectra.